Kinematic Analysis of Lower Extremity Movement Patterns During Functional Tests in Collegiate Track and Field Runners to Predict Injury Incidence - Maddie Hoyt; Brooke Parker; Bailey Weise; Andrew Busch (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
OBJECTIVE Lower extremity overuse injuries are becoming increasingly more prevalent in endurance-based running sports. These injuries negatively impact an athlete’s sports performance and increase the risk of additional injuries. The purpose of this study was to first examine kinematic and kinetic variables within distance runners and compare those with previous lower extremity injuries to those without reported injuries; and second to understand if such variables predicted future injuries sustained throughout a track season.